1971
DOI: 10.1021/ja00747a047
|View full text |Cite
|
Sign up to set email alerts
|

So-called "ladder structure" of equilibrated phenylsilsesquioxane

Abstract: Table . Metal-Promoted Isomerizations of l-Methyltricyclo[4. .1.0.0* '7]heptane Catalyst Conditions temp, time, solvent a ch3 11 -% yield of products-,ch3 cc d ch3 12 13 CH, 'to 14 [Rh(CO)iCl]i 25°, 15 min, CHC1, 96 [Ir(CO)sCl]i 25°, 14 hr, CHC1, 93

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 2 publications
0
55
0
2
Order By: Relevance
“…On the other hand, with respect to the polysilsesquioxane ladder, Brown et al [13] first reported the synthesis of a soluble polyphenylsilsesquioxane ladder by means of an "equilibration polymerization" method in 1960. However, his result was refuted 11 years later by Frye et al, [14] who pointed out that the polyphenylsilsesquioxane ladder is not a complete ladderlike polymer, but "partially opened polycyclic cages". In 2004, Yamamoto et al [15] reported an oligomeric polyphenylsilsesquioxane ladder with low ladder regularity.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, with respect to the polysilsesquioxane ladder, Brown et al [13] first reported the synthesis of a soluble polyphenylsilsesquioxane ladder by means of an "equilibration polymerization" method in 1960. However, his result was refuted 11 years later by Frye et al, [14] who pointed out that the polyphenylsilsesquioxane ladder is not a complete ladderlike polymer, but "partially opened polycyclic cages". In 2004, Yamamoto et al [15] reported an oligomeric polyphenylsilsesquioxane ladder with low ladder regularity.…”
Section: Introductionmentioning
confidence: 95%
“…1 Its unique double-chain ladderlike structure, which results in film-forming ability, thermal stability and mechanical property, and so forth, different from those of more classical polymers, has interested many polymer chemists. [2][3][4][5][6][7][8][9] However, this polymerization method cannot be used to synthesize reactive ladderlike polysilsesquioxanes such as ladderlike polyhydrosilsesquioxane (H-T) and polyvinyl(or allyl)silsesquioxane (Vi-T or Allyl-T) due to its harsh reaction conditions (at 250°C in the presence of KOH).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their solubility, ladder structures have been proposed 123. However, viscosity studies by Frye [3] indicate that the polyphenylsilsesquioxane is more likely best represented by a polymer rich in both cyclic structures and branches, but without any regular stereochemistry.…”
Section: Introductionmentioning
confidence: 99%